Long‐term evolution of the Old Rhine estuary: Unravelling effects of changing boundary conditions and inherited landscape. (2nd January 2019) - de Haas, Tjalling; van der Valk, Lambertus; Cohen, Kim M.; Pierik, Harm Jan; Weisscher, Steven A. H.; Hijma, Marc P.; van der Spek, Ad J. F.; Kleinhans, Maarten G.
Abstract: The long‐term morphodynamic evolution of estuaries depends on a combination of antecedent topography and boundary conditions, including fluvial input, sea‐level change and regional‐landscape interactions. Identifying effects of such boundary conditions on estuary evolution is important to anticipate future changes in specific boundary conditions and for hindcasting with numerical and physical models. A comprehensive synthesis of the evolution of the former Old Rhine estuary is presented here, together with its boundary conditions over its full lifespan from 6, 500 to 1, 000 cal. yr bp . This system formed during a period of sea‐level high stand, during which the estuary served as the main River Rhine outlet. The estuary went through three stages of evolution: a maturation phase in a wide infilling back‐barrier basin, a stable mature phase and an abandoning phase, both in a laterally confined setting. The Old Rhine River formed by a river avulsion around 6, 500 cal. yr bp that connected to a tidal channel within a large back‐barrier basin. Decelerating sea‐level rise caused the back‐barrier basin to silt up around 5, 700 cal. yr bp, resulting in shoreline progradation by beach‐barrier formation until ∼ 2, 000 cal. yr bp . Beach‐barrier formation along the coast and natural levee formation along the river triggered peat formation in the coastal plain, laterally constraining the estuary and limiting overbank deposition, which caused most sediment to accumulate offshore. The abandoning phase started around 2, 200 cal. yr bp when a series of upstream avulsions led to a substantial reduction in fluvial input. This induced a period of enhanced estuarine overbank clay deposition that continued into near‐complete silting up and estuary closure around 1200 ad . These findings exemplify how tidal systems, formed in wide coastal plains during sea‐level high stand, depend on antecedent conditions, and how they respond to connection and disconnection of a large river over long, millennial timescales. Abstract : We present a comprehensive synthesis of the evolution of the former Old Rhine estuary and its boundary conditions over its full lifespan from 6, 500 to 1, 000 yr bp . The estuary went through three stages of evolution: a maturation phase in a wide infilling back‐barrier basin, a stable mature phase and an abandoning phase, both in a laterally confined setting. The evolution of the Old Rhine estuary exemplifies how tidal systems, formed in wide coastal plains during sea‐level high stand, depend on antecedent conditions, and how they respond to connection and disconnection of a large river over long, millennial, timescales.